Resilience during the Lockdown: Insignificance of Perceived Social Support - Sheng Yee Wan; Cherilyn Nicole Rhui Yen Yeo; Shi Qi Foo; Kususanto Ditto Prihadi (International Journal of Public Health Science (IJPHS), 2022)
Pre-pandemic studies had established that human resilience is mainly based on the social feedback that enables the formation of one’s perceived social support. In the Malaysian context, the enforcement of the movement control order (MCO) amidst the pandemic altered the social interaction pattern. The shift had involved more dependence on online communication (i.e., social media). Therefore, the way perceived social support (PSS) plays its role in predicting resilience could have been affected. Due to the reason mentioned above and the reports that Malaysians tend to increase their levels of spirituality during the MCO, we hypothesized that the sense of being empowered fully mediates the contribution of PSS on resilience while moderated by the levels of spirituality. Four hundred and five adults who reside in Malaysia during the MCO 2 were recruited to respond to scales of perceived social support, spirituality, empowerment, and resilience through the online survey. Our results suggested that the sense of empowerment significantly and fully mediated the relationship between PSS and resilience among individuals with low and moderate levels of spirituality. Scope, limitations, implications, and suggestions were also discussed at the end of this paper.